Breast cancer burden in central Sudan - Elgaili M Elgaili; Dafalla O Abuidris; Munazzah Rahman; et al (Dove Medical Press, 2010)
Elgaili M Elgaili1, Dafalla O Abuidris2, Munazzah Rahman3, Arthur M Michalek4, Sulma I Mohammed3,51Faculty of Medicine, Department of Pathology, University of Gezira, Sudan; 2Radiation Oncology Department, Institute of Nuclear Medicine and Oncology, University of Gezira, Sudan; 3Department of Comparative Pathobiology, Purdue University, West Lafayette, IN USA; 4Roswell Park Cancer Institute, Buffalo, NY, USA; 5Purdue Cancer Center, Purdue University, West Lafayette, IN, USAAbstract: Breast cancer is a worldwide disease resulting in many deaths. Although breast cancer incidence is lower in Sub-Saharan African countries than in developed countries, African women are more likely than women in the developed world to be diagnosed at later stages of the disease and, thus, are more likely to die from it. This is due to the lack of awareness by women, accessibility to screening methods, and availability of African-based research findings that would influence decision making at the governmental level. This descriptive study was undertaken to shed light on the type, stage and age distribution of breast cancer at diagnosis in women living in central Sudan encompassing al-Gezira, Blue Nile, White Nile, and Sennar States. Cases comprised 1255 women from central Sudan diagnosed with breast cancer and referred to and treated at Institute of Nuclear Medicine, Molecular Biology, and Oncology, from January 1999 to December 2006. Data revealed that 74% of the women were <50 years old or premenopausal. Invasive ductal carcinoma was the most common pathology (82%) and women presenting with stage III or higher tumors that had already metastasized, while ductal carcinoma in situ was the least prevalent (0.5%) finding. Estrogen and progesterone receptors expression were performed on a limited number of samples and the overwhelming majority of cases were observed to be negative for estrogen and progesterone receptors expression.Keywords: female breast cancer, estrogen receptor, progesterone receptor, epidemiology, Africa